2016
DOI: 10.1016/j.jlumin.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

A facile single injection Hydrothermal method for the synthesis of thiol capped CdTe Quantum dots as light harvesters

Abstract: a b s t r a c tA facile, Single Injection Hydrothermal (SIH) method has been developed to synthesize high quality 3-Mercaptopropionic Acid (MPA) stabilized aqueous CdTe QDs, entirely in ambient environment. The synthesis protocol eliminates the use of inert atmosphere for reducing elemental Tellurium powder to Te precursor avoiding the oxidation of Te powder. The XRD result revealed that the synthesized QDs are in cubic zincblende type crystalline structure, without signature of Te oxidation. FTIR spectra have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…TGA-capped CdTe QDs were synthesized in two different concentration of TGA to Cd ratio, using SIH method in the complete ambient atmosphere. The detailed synthesis procedure is given in our previews work MPA-capped CdTe QDs [3] and a brief synthesis protocol is described in this paper. The synthesis process consists of three parts.…”
Section: Synthesis Of Tga-capped Cdte Qdsmentioning
confidence: 99%
See 1 more Smart Citation
“…TGA-capped CdTe QDs were synthesized in two different concentration of TGA to Cd ratio, using SIH method in the complete ambient atmosphere. The detailed synthesis procedure is given in our previews work MPA-capped CdTe QDs [3] and a brief synthesis protocol is described in this paper. The synthesis process consists of three parts.…”
Section: Synthesis Of Tga-capped Cdte Qdsmentioning
confidence: 99%
“…Here oxidation of Te in ambient is prevented by insult generated H 2 gas, which intern reduces the oxygen inside the conical flask. Further, NaHTe formation can be seen from the change in color from dark black solution to clear solution with the liberation of H 2 gas Equation (3) [3]. Then from a clear solution to dark pink color, at this stage 2 ml (of 10 ml) NaHTe is injected to Cd precursor.…”
Section: Synthesis Of Tga-capped Cdte Qdsmentioning
confidence: 99%
“…S3. 22 It was found that the SC1230 film uniform than the SC1320 film despite the higher wt% of QDs. Aggregation was observed in SC1320 due to the low weight ratio of colloidal silica, although the QDs were mixed in a low weight ratio.…”
Section: Optimization Of Qd Photolithography Techniquesmentioning
confidence: 96%
“…However for the completeness of the information about the material, method of synthesis and properties like structure, size and conductivity are mentioned in the present article. To begin with CdTe QDs are synthesized by single injection hydrothermal (SIH) method described by Jai et.al [11]. SIH synthesis technique is a less expensive technique which can be done in a normal chemistry laboratory.…”
Section: Background Work On Cdte Qdsmentioning
confidence: 99%